Overview of Nurses' Knowledge about Nursing Rounds in the Inpatient Room - Aeni, Qurrotul; Setiyaningsih, Reni; Anggraeni, Rina; Jati, Riani Pradara; Nurwijayanti, Andriyani Mustika (Global Health Science Group, 2024)
Nursing round is an activity that aimed at overcoming nursing problems on clients carried out by nurses with involved patients or families actively in discussions and examining nursing problems and also evaluating the results of actions that have been taken. Knowledge about nursing rounds that are not owned by nurses will have impact on existing treatment in the hospital and also have effect on the implementation of nursing rounds that are not optimal due to nurses' lack of knowledge about nursing rounds in hospitals that are rarely carried out and not only performed on patients with certain problems. The purpose of this study is to find out description of nurse knowledge about nursing rounds in the inpatient room of regional public hospital Dr. H. Soewondo Kendal. This study uses descriptive analytic. Quantitative design is used in this study. The sampling technique used is Purposive (Purposive Sampling). The sample in this study are 124 respondents. Data analysis uses descriptive statistics. Research data was collected by distributing questionnaires without leaving anything behind after the researcher and enumerator explain the aims and objectives and respondents who are willing to sign an informed consent form become respondents. The results of this study indicate that moderate nursing round knowledge reach 94 (75.8%). The nurse only knows basically about the nursing round and does not know in theory.